Prevalence of HIV in antenatal women at GMERS Medical College Sola, Ahmedabad - Patel, Seema Kalpesh; Kansara, Vijay; Aanand, Nikhil; Muchhadia, Jeetesh; Patel, Riddhi; Kagathra, Bhoomika; Mehta, Riddhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Estimating the seroprevalence of HIV in a low risk population such as pregnant women provides essential information for an effective implementation of AIDS control programmes, and also for the monitoring of HIV spread within a country. Few studies are available from Gujarat, India showing the current trend in HIV prevalence in the antenatal population; which led us to carry out this study at a tertiary care hospital in GMERS medical college, Sola, Ahmedabad, India. Methods: This is a retrospective study. Total 8224 antenatal patients, who attended for first time at antenatal OPD at GMERS Medical College, Sola between April 2012 to March 2014, were included in the study. HIV testing was done by RAPID method after taking informed consent and pre-test counselling as per NACO guideline. Results: Out of total 8224 antenatal patients 7921 (96%) patient opted for HIV testing. Seroprevalence of HIV is found to be 15/7921 (0.19%). 7044/7921 (88.93%) women attended post-test counselling. 12/15 (80%) HIV positive women accepted post-test counselling.12/15 (80%) spouses accepted testing for HIV. 8/12 (66.66%) spouses of HIV positive women were also found to be HIV positive. Conclusions: The seroprevalence of HIV infection in antenatal women is low.